Electron beam immobilization of functionalized poly(vinyl methyl ether) thin films on polymer surfaces – Towards stimuli responsive coatings for biomedical purposes (eXPRESS Polymer Letters)
Thin films of poly(vinyl methyl ether) (PVME) were immobilized on polystyrene surfaces by low energy electron beam cross-linking. Structure retention as well as the thermo-responsive swelling behavior in aqueous media were studied by attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR) and spectroscopic ellipsometry respectively. The physical properties of the thermo-responsive coatings can be controlled in a wide range by adjusting the irradiation parameters. To allow for a variety of biomolecular functionalization strategies, the concept was extended by adding reactive sites to the system. For that purpose a mixture of PVME and the copolymer of PVME and maleic acid was applied, that possesses a similar stimuli-responsive behavior.